2010
DOI: 10.1111/j.1095-8649.2009.02527.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and structure of egg envelopes in Russian sturgeon Acipenser gueldenstaedtii (Acipenseriformes: Acipenseridae)

Abstract: The covering of the eggs in Russian sturgeon Acipenser gueldenstaedtii consists of three envelopes (the vitelline envelope, chorion and extrachorion) and is equipped with multiple micropyles. The most proximal to the oocyte is the vitelline envelope that consists of four layers of filamentous and trabecular material. The structural components of this envelope are synthesized by the oocyte (primary envelope). The chorion encloses the vitelline envelope. The extrachorion covers the external surface of the egg. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…Most oocytes in gonads were in previtellogenic stages of growth and only a few ovarian follicles formed egg envelopes and gathered yolk (¯ELAZOWSKA et al 2007;¯ELA- ZOWSKA & KILARSKI 2009;¯ELAZOWSKA 2010). Such fish should not be used for reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most oocytes in gonads were in previtellogenic stages of growth and only a few ovarian follicles formed egg envelopes and gathered yolk (¯ELAZOWSKA et al 2007;¯ELA- ZOWSKA & KILARSKI 2009;¯ELAZOWSKA 2010). Such fish should not be used for reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs of sturgeons including the investigated species, Acipenser gueldenstaedtii and Acipenser baerii, are equipped with multiple micropyles lo-cated at the animal region that allow entry of numerous spermatozoa (CHERR & CLARK 1982;DEBUS et al 2008;PSENICKA et al 2010;¯ELAZOWSKA 2010). Observation of egg surfaces in A. transmontanus and in A. baerii during gamete fusion revealed that after incorporation of a spermatozoon, the contents of cortical granules was released into the space between the oocyte and egg envelope.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pelagic eggs usually possess a thin follicular epithelium layer and zona radiata, while demersal eggs are covered by a thicker follicular epithelium layer and a comparatively more complex egg envelope (Stehr & Hawkes 1979). The egg envelope protects the egg from mechanical forces such as water currents (Riehl & Patzner 1998;Esmaeili & Johal 2005;Mansour et al 2009a,b), predators (Riehl & Patzner 1998;Rizzo et al 2002) and bacterial and fungal infection (Paxton & Willoughby 2000;Zelazowska 2010). The egg envelope also acts as a diffusion barrier to chemicals and environmental pollutants (Esmaeili & Johal 2005).…”
Section: Fish Egg Structure and Their Adhesive Propertiesmentioning
confidence: 99%
“…The egg envelopes of these sturgeon species have not been studied very systematically. Whereas the structure of the membranes has been thoroughly studied in wild sturgeon (Sadov, ; Vorobyova and Markov, ; Zelazowska, ), investigations of cultured sturgeons refer mainly to the sizes of oocytes and their dimensions as well as to the structure of nuclei and micropyles (Hurvitz et al., ; Mikodina and Novosadova, ).…”
Section: Introductionmentioning
confidence: 99%